Kinerja Asisten Apoteker Lulusan Smk Farmasi Di Bidang Pekerjaan Kefarmasian (Studi Kasus Di Beberapa Apotek Kota Salatiga) - SANTOSO, HARTANTO BUDI (2016)
ABSTRACT Hartanto Budi Santoso, NIM : Q100130116. Performance Assistant Pharmacist Pharmacy Vocational Graduates In The Pharmaceutical Works (Case Study in Some pharmacies Salatiga). Thesis Master of Adminitration Education, the Graduate School ofthe University of Muhammadiyah Surakarta, 2015. Vocational High Schoolof Pharmacy as an institution that educates and scored graduates called Assistant Pharmacist required to produce a reliable output, so it has good performance in the field of pharmacy. For the learning process takes place shall forward the debriefing skills and abilities in the field of pharmacy. The research objective is to describe the performance of the vocational school graduates Pharmacy pharmacist's assistant in performing work of pharmacy services in pharmacies and administrative management work in pharmacies, which in turn indicates the performance of the graduates of vocational Pharmacy pharmacist's assistant who works in a pharmacy. This research method is done by interviews, observations and collecting data is written. This is a qualitative research, and naturalistic research-phenomenological approach. The data in this study, there are two primary data obtained through semistadradized interviews, while the secondary data obtained by collecting written information. Semistandardized interviews were conducted with Section Pharmaceutical, Food and Beverage Salatiga City Health Department, Pharmacy Pharmacist business / pharmacy Pharmacy Manager in fourth place of research, the Union of Pharmacist Indonesia Salatiga and customers in fourth place to study pharmacy. While writing the data obtained from the Registration Section, Accreditation and Health Utilization Salatiga City Health Department, as well as checklists of questions addressed to the Pharmacy and Pharmacist business customers pharmacy. Validity of the data in this study is done through observation, triangulation of data (pharmacists and customers) as well as informants review. Technical analysis of the data performed by the data analysis models Spradley, namely domain analysis, taxonomy analysis, component analysis and thematic analysis. The results showed the performance assistant pharmacist Pharmacy Vocational High School graduates in the work of pharmacy services in the pharmacy has not shown good performance, only one aspect of the six aspects that show a good performance on this aspect of the job is changing the form of the drug and drug manufacturing. Similarly, in a job in pharmacy administration has not shown a good performance, it is because in addition to unskilled, the assistant pharmacist Pharmacy Vocational High School graduates only received a small portion of the work in a job in pharmacy administration. Thus the performance of the assistant pharmacists Pharmacy Vocational High School graduate who works in a pharmacy is not good or not satisfactory. In addition, the assistant pharmacists Pharmacy Vocational High School graduates who have recently graduated are also not ready to work in the world of work.